2021
DOI: 10.1002/ps.6339
|View full text |Cite
|
Sign up to set email alerts
|

Can the banana weevil Cosmopolites sordidus be a vector of Fusarium oxysporum f.sp. cubense race 1? Unravelling the internal and external acquisition of effective inoculum

Abstract: BACKGROUND With the undergoing world outbreak of Fusarium wilt of bananas, it is essential to unravel all the possible process of dissemination of this disease. The host‐pest interactions of the banana weevil with banana plants make this insect an important potential vector. This study, carried out in controlled conditions, explores the interaction between the banana weevil and Fusarium oxysporum f.sp. cubense race 1 (Foc), with a focus on the external and internal transport of viable fungal propagules. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…This effect of those soil properties could have played a role in the devastation of Gros Michel by Foc Race 1 in Latin America during the last century. The decimation of the former main banana subgroup (the Gros Michel) appears expectable with the incipient knowledge about the fungus and its dissemination (Dita et al 2018) and the recently reported interactions of Foc with e.g., soil nematodes (Rocha et al 2020) and the banana weevil (Guillén et al 2021). Due the lack of awareness about the importance of tested soil properties in the expression of the disease, the standard management of the crop with the common application of high rates of N (and the consequent drop of pH) could increase the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of those soil properties could have played a role in the devastation of Gros Michel by Foc Race 1 in Latin America during the last century. The decimation of the former main banana subgroup (the Gros Michel) appears expectable with the incipient knowledge about the fungus and its dissemination (Dita et al 2018) and the recently reported interactions of Foc with e.g., soil nematodes (Rocha et al 2020) and the banana weevil (Guillén et al 2021). Due the lack of awareness about the importance of tested soil properties in the expression of the disease, the standard management of the crop with the common application of high rates of N (and the consequent drop of pH) could increase the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fungal propagules can be found in the digestive system or the feces of these animals of different trophic levels [5,13]. Furthermore, the propagules can adhere to the exoskeleton (ectozoochory) of the arthropods while they move between infected plant material [14,15]. Moyo et al [5] found on herbivory and on predatory arthropods phytopathogenic fungi and showed that herbivore species transmitted the pathogen to healthy plants and that their feces are a source for inoculation.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that feral pigs surrounding the fields [ 53 ] and humans [ 54 ] are involved in the within and among field dispersal of Foc [ 7 , 21 ]. Insects as weevil borers can carry infective propagules of Foc [ 55 ] and their populations were driving FWB epidemics in banana fields [ 19 ].…”
Section: Discussionmentioning
confidence: 99%